VALES I: the molecular gas content in star-forming dusty H-ATLAS galaxies up to z = 0.35 - Villanueva, V.; Ibar, E.; Hughes, T.M.; Lara-Lopez, M.A.; Dunne, L.; Eales, S.; Ivison, R.J.; Aravena, M.; Baes, M.; Bourne, N.; Cassata, P.; Cooray, A.; et al. (Oxford University Press, 2017)
We present an extragalactic survey using observations from the Atacama Large Millimeter/submillimeter Array (ALMA) to characterize galaxy populations up to z = 0.35: the Valpara´ıso ALMA Line Emission Survey (VALES). We use ALMA Band-3 CO(1–0) observations to study the molecular gas content in a sample of 67 dusty normal star-forming galaxies selected from the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS). We have spectrally detected 49 galaxies at >5σ significance and 12 others are seen at low significance in stacked spectra. CO luminosities are in the range of (0.03–1.31) × 1010 K km s−1 pc2, equivalent to log(Mgas/M) = 8.9–10.9 assuming an αCO = 4.6 (K km s−1 pc2) −1, which perfectly complements the parameter space previously explored with local and high-z normal galaxies. We compute the optical to CO size ratio for 21 galaxies resolved by ALMA at ∼3.5 arcsec resolution (6.5 kpc), finding that the molecular gas is on average ∼ 0.6 times more compact than the stellar component. We obtain a global Schmidt–Kennicutt relation, given by log[[ΣSFR/(M yr−1 kpc−2)] = (1.26 ± 0.02) × log[ΣMH2 /(M pc−2)] − (3.6 ± 0.2). We find a significant fraction of galaxies lying at ‘intermediate efficiencies’ between a longstanding mode of star formation activity and a starburst, specially at LIR = 1011–12 L. Combining our observations with data taken from the literature, we propose that star formation efficiencies can be parametrized by log [SFR/MH2 ] = 0.19 × (log LIR − 11.45) − 8.26 − 0.41 × arctan[−4.84 (logLIR − 11.45)]. Within the redshift range we explore (z < 0.35), we identify a rapid increase of the gas content as a function of redshift.